2012
DOI: 10.1074/jbc.m111.335927
|View full text |Cite
|
Sign up to set email alerts
|

Protein Inhibitor of Activated STAT3 (PIAS3) Protein Promotes SUMOylation and Nuclear Sequestration of the Intracellular Domain of ErbB4 Protein

Abstract: Background: Mechanisms regulating nuclear translocation of the ErbB4 intracellular domain (ICD) are unclear. Results: PIAS3 interacts with ErbB4, sequesters ICD into the nucleus, and represses its nuclear signaling. Conclusion: PIAS3 is a regulator of subcellular localization and nuclear functions of ErbB4. Significance: A novel mechanism controlling the signaling of an ICD of a receptor tyrosine kinase in the nucleus is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
44
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 45 publications
5
44
0
Order By: Relevance
“…The biology of the PIAS3 protein is not fully clear. Originally described as a STAT3-specific inhibitor (38), it also blocks the microphthalmia transcription factor (39), acts as a SUMOylation cofactor for nuclear receptors, and binds to the intracellular domain of ErbB4 to enhance its nuclear retention (40). Unlike SOCS3 and PIAS3, which block the acute cytokineinduced responses, GRIM-19 blocks oncogene-induced cellular transformation and acts against chronically active STAT3 (41).…”
Section: Discussionmentioning
confidence: 99%
“…The biology of the PIAS3 protein is not fully clear. Originally described as a STAT3-specific inhibitor (38), it also blocks the microphthalmia transcription factor (39), acts as a SUMOylation cofactor for nuclear receptors, and binds to the intracellular domain of ErbB4 to enhance its nuclear retention (40). Unlike SOCS3 and PIAS3, which block the acute cytokineinduced responses, GRIM-19 blocks oncogene-induced cellular transformation and acts against chronically active STAT3 (41).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, SUMO modification of these proteins at their NLS or SUMOylation of other proteins at non-NLS sites, including actin, SENP1, ErB4, and Smad4, promotes their localization to the nucleus (23)(24)(25)(26). However, it is unclear whether this is because their SUMOylation leads to nuclear localization or if SUMOylation prevents these proteins from being exported to the cytoplasm.…”
mentioning
confidence: 99%
“…It has previously been shown that the IGF-1R and ErbB-4 are SUMOylated by SUMO-1 (8,23). SUMOylated proteins were initially reported to be expressed in the cell nucleus, but later also in other parts of the cell (18).…”
Section: Egfr Is Sumoylatedmentioning
confidence: 99%
“…Recently, the insulin-like growth factor 1 receptor (IGF-1R) and ErbB-4 were shown to be modified by SUMO-1 and upon SUMOylation the receptors become stabilized and translocated into the cell nucleus (8,23,24).…”
mentioning
confidence: 99%